Association between intimate partner violence and depressive symptoms in the first postpartum year in Peru - Muñoz-Callupe, Shantal Rosa (2025)
Objective: To evaluate the relationship between intimate partner violence (IPV) in the past year and the development of depressive symptoms within twelve months postpartum in women aged 15 to 49. Materials and Methods: A descriptive, analytical, cross-sectional, and secondary study using data from the 2021-2023 Demographic and Family Health Survey – ENDES surveys. The subsample included women aged 15-49 in their first postpartum year. A complex sample analysis was performed using prevalence estimates, chi-square tests, and multiple regression models. Results: The subsample included 5,903 women, with a prevalence of postpartum depressive symptoms (PDS) of 6.32% (95% CI: 5.40-7.40). Intimate partner violence affected 19.23% (95% CI: 17.68-20.88) of postpartum women during their first year, and victims had 4.53 times higher odds of developing PDS after adjusting for sociodemographic factors (aOR: 4.53; 95% CI: 2.99-6.88). Conclusions: There is a significant prevalence of PDS and IPV among women in their first postpartum year. The presence of IPV, in any of its forms, significantly increases the likelihood of developing PDS, underscoring the importance of systematic IPV screening during the postpartum period and timely psychological support.